A bi-level multi agent based protection scheme for distribution networks with distributed generation. (November 2019) - Abbaspour, Ehsan; Fani, Bahador; Heydarian-Forushani, Ehsan
Highlights: The paper proposes a protection scheme to coordinate protective equipment in presence of DGs. This scheme mitigates the dependency to the network collected information. The protection scheme includes both the relay and DG agents in two separate levels. It improves the conventional MAS protection scheme in terms of performance and operation speed. Abstract: This paper proposes a bi-level multi agent system-based protection scheme with the aim of maintaining the coordination of over current relays in the presence of Distributed Generation (DG) resources. In the proposed scheme, the distribution network protection has been divided into two levels so that the first level protection is implemented through relay agents which are participated in the protection scheme via exchanging information to each other. The second protection level is performed by generation agents when the fault still remains and the first level protection is not effective. To this end, the generation agents are categorized into the main and distributed zones and perform the protection through sharing information together. The effectiveness of the proposed model is examined through several simulation studies on a practical distribution network.